2022
DOI: 10.33961/jecst.2021.00535
|View full text |Cite
|
Sign up to set email alerts
|

A LiPF6-LiFSI Blended-Salt Electrolyte System for Improved Electrochemical Performance of Anode-Free Batteries

Abstract: ANODE-free Li-metal batteries (AFLMBs) operating with Li of cathode material have attracted enormous attention due to their exceptional energy density originating from anode-free structure in the confined cell volume. However, uncontrolled dendritic growth of lithium on a copper current collector can limit its practical application as it causes fatal issues for stable cycling such as dead Li formation, unstable solid electrolyte interphase, electrolyte exhaustion, and internal short-circuit. To overcome this l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…However, the dendritic growth of lithium metal, which leads to battery failure, remains a problem 5 . A solid-electrolyte interphase (SEI) having high mechanical strength was reported to be effective in preventing dendrite formation 6,7 . Such an SEI layer stops unwanted reactions between the electrolytes and lithium metal and prevents dendrite growth to conserve the lithium metal source.…”
mentioning
confidence: 99%
“…However, the dendritic growth of lithium metal, which leads to battery failure, remains a problem 5 . A solid-electrolyte interphase (SEI) having high mechanical strength was reported to be effective in preventing dendrite formation 6,7 . Such an SEI layer stops unwanted reactions between the electrolytes and lithium metal and prevents dendrite growth to conserve the lithium metal source.…”
mentioning
confidence: 99%
“…Figure 12d-f show that the LiNO 3 -VC dual additive exhibits improved performance in terms of coulombic efficiency and ion transfer resistance [114]. In addition, a study showing the synergy effect of LiFSI, LiPF 6 and LiNO 3 in a carbonate-based electrolyte has been reported [116].…”
Section: Carbonate-based Electrolytesmentioning
confidence: 91%
“…The concentration ratios are also essential for highly concentrated dual-salt systems. Kim and coworkers examined the effectiveness of the LiPF 6 +LiFSI dual-salt carbonate-based electrolyte system with various concentrations [112]. The authors demonstrated that a mixed salt ratio of LiPF 6 /LiFSI > 1 resulted in limited capacity retention of the assembled AFLBs.…”
Section: Dual-salt Electrolytesmentioning
confidence: 99%